Developing Students’ Creativity in Writing Poetry through Technology-Mediated Task-Based Language Teaching - Sulastri, Fera; Hartono, Rudi; Yuliasri, Issy; Astuti, Puji (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aims to report the enhancement of the students' creativity in writing poetry through the Technology-Mediated Task-Based Language Teaching (TM-TBLT) model. The research is based on the result of a pre-questionnaire showing the low confidence of students when writing poetry in English because of a lack of vocabulary, difficulty in selecting aesthetically pleasing words, and minimal exposure to studying poetry in their curriculum. Through the implementation of TM-TBLT in the Creative Writing course, this study examines how digital technology can be utilized to enhance students' creativity in writing poetry. Two-cycle action research is used by the study. The first cycle seeks to reinforce the students' confidence in poetry writing using Blackout Poetry, while the second cycle seeks to build their creative language play ability by writing haiku. Data collection was conducted by observing, interviewing, and analysing documents related to the poetry of the students. The findings indicate that TM-TBLT significantly enhances the creative ability of students in five aspects, including idea integration, rhyme, figurative language, imagery, and lineation. The use of technology such as Blackout Poetry Maker, Canva, QR codes, and cell phone cameras enables deeper investigation of language and increases student engagement in creative writing. The study discovers that TM-TBLT can be a very effective approach to teaching creative writing in EFL settings. By integrating technology into task-based learning, not only do the students enhance their writing skill but also become more creative and forceful in communication through poetry.